2016
DOI: 10.1016/j.devcel.2016.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Transposable Elements and Their KRAB-ZFP Controllers Regulate Gene Expression in Adult Tissues

Abstract: KRAB-containing zinc finger proteins (KRAB-ZFPs) are early embryonic controllers of transposable elements (TEs), which they repress with their cofactor KAP1 through histone and DNA methylation, a process thought to result in irreversible silencing. Using a target-centered functional screen, we matched murine TEs with their cognate KRAB-ZFP. We found the paralogs ZFP932 and Gm15446 to bind overlapping but distinguishable subsets of ERVK (endogenous retrovirus K), repress these elements in embryonic stem cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
202
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 200 publications
(217 citation statements)
references
References 60 publications
13
202
0
2
Order By: Relevance
“…HERVs and LINEs). Conversely, many TE subfamilies are recognized by several KRAB-ZFPs, which most often target clearly distinct regions of their integrants, as has been observed for ERVKs (endogenous retrovirus K) in mouse and for HERVs and LINE-1s (L1s) in humans Ecco et al, 2016). Interestingly, in humans, it was observed that the age of the elements influences their pattern of KRAB-ZFP recruitment.…”
Section: Genomic Targets Of Human Krab Zinc Finger Proteinsmentioning
confidence: 93%
See 3 more Smart Citations
“…HERVs and LINEs). Conversely, many TE subfamilies are recognized by several KRAB-ZFPs, which most often target clearly distinct regions of their integrants, as has been observed for ERVKs (endogenous retrovirus K) in mouse and for HERVs and LINE-1s (L1s) in humans Ecco et al, 2016). Interestingly, in humans, it was observed that the age of the elements influences their pattern of KRAB-ZFP recruitment.…”
Section: Genomic Targets Of Human Krab Zinc Finger Proteinsmentioning
confidence: 93%
“…It was then suspected that the primary role of KRAB-ZFPs was to silence TEs, and that their evolutionary selection represented the host component of an arms race against these genetic invaders (Jacobs et al, 2014;Castro-Diaz et al, 2014;Thomas and Schneider, 2011). More recent data, however, suggest that KRAB-ZFPs fulfill a role that is far more elaborate and, in some cases at least, can contribute to the domestication of their TE targets for the benefit of the host (Ecco et al, 2016;Imbeault et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition or alternatively, possible variegated or lack of ERV repression might relate to the rather low to moderate expression of the two KRABcontaining zinc finger proteins Zfp932 and Gm15446 in wild-type GV oocytes. These KRAB-ZFPs have recently been shown to control repression of various ERVK elements, known to also be silenced by Kap1 (also known as Trim28 or Tif1beta) and Setdb1 (Ecco et al, 2016).…”
Section: Discussionmentioning
confidence: 99%